Age-related changes of the cerebral ventricles of healthy domestic cats - Babicsak, Viviam R. [UNESP]; Klein, Adriana V. [UNESP]; Tsunemi, Miriam H. [UNESP]; Vulcano, Luiz C. [UNESP] (FapUNIFESP (SciELO), 2018)
This study aimed to determine age-related changes of the cerebral ventricles of healthy non-brachycephalic domestic cats by the acquisition of brain MRI images of 12 adult (1 to 6 years), 11 mature (7 to11 years) and 10 geriatric (12 years or more) cats. Our hypothesis is that the cerebral ventricular system of cats expands with increasing age. The possibility of the evidence of the olfactory bulb cavities and temporal horns of the lateral ventricles were evaluated in this study. Volumes of the olfactory bulb cavities, lateral ventricles (including the temporal horns), third ventricle, mesencephalic aqueduct and fourth ventricle were measured and corrected for the intracranial volume. Significant differences were found between the adult and mature groups in relation to the geriatric one for the variable related to the evidence of the temporal ventricular horns, which were most frequently visualized in geriatric cats. Percentage of the right lateral and third ventricles volume by intracranial volume were significantly higher in geriatric cats compared to the adults. The results of this study demonstrate that ventricular dilation tends to occur with advancing age in cats, as well as the increase in the frequency of the temporal ventricular horn evidence, as had been indicated in the hypothesis of the study.
Keywords: Aging; Brain; Cats; Cerebral ventricles; Dilation; Magnetic resonance imaging; Morphology; Neuroanatomy